Performance analysis of a free space optics link with multiple transmitters/receivers - Md Noor, Nur Haedzerin; Naji, Ahmed Wathik; Al-Khateeb, Wajdi Fawzi Mohammed (IIUM Press, 2012)
Multiple transmitters/receivers (TX/RX) are used to improve the quality of Free Space Optics (FSO) communication system. With the current needs of this technology for longer distance, the qualitative analysis of the system has become essential. In this work, the received power level (PR) and bit error rate (BER) are considered to determine the FSO link performance. The relationship between the two parameters are investigated and analyzed. Furthermore, the received power for various number of TXs and RXs are experimentally measured and compared with the theoretical value calculated. The first part of the work deals with the theoretical calculation and simulation designs of the multiple laser beams based on the commercial FSO on the practical site. The second part is the practical work and the latter part is the analysis of the system performance.